Study on the variability of printed documents produced by laserjet Printers (hp laserjet p3005 printers) - Kamaluddin, Mohammad Rahim (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
This study looks at the variability of prints produced by LaserJet printers. Five HP LaserJet P3005 printers were used to print out a letter consisting of a mixed of letters and numbers at different fonts. Seven duplicates were printed from each printer and compared using a stereomicroscope. Printed samples were also obtained from two selected printers in time interval of a week over a period of about a month. Results based on microscopic examination by stereomicroscope on the printed documents from some printers of same brand and model had shown specific characterizations. Some specific individual patterns are shared by a subgroup of printers that used in our study. Though, it is difficult to link such printed material to an individual printer, this study helps to include or exclude the possible source of the printer from same brand and model. Microscopic examination on the printed documents printed over a period of four weeks revealed the drastic changes between first week and third or fourth week in terms of the thickness of the alphabets appears to be caused by insufficient toner. Hence, it enables to determine the order of printed materials in terms of the time interval of a few weeks. This study agrees with previous reported observation stating that individual characterization of the printed documents can be used to link a document to at least a group of possible printers.